Effects of Strain Ratio on Fatigue Behavior of G20Mn5QT Cast Steel - 韩庆华 郭琪 尹越 邢颖 (Transactions of Tianjin University, 2016)
Due to traffic and wave actions, cast steel joints are subjected to variable-amplitude fatigue loading, which may cause fatigue problems. The ratio of the minimum strain to the maximum strain （strain ratio）can be em- ployed to analyze the influence of variable-amplitude fatigue both in the elastic and plastic ranges. To evaluate the effect of the strain ratio on G20Mn5QT cast steel, the fatigue tests of smooth specimens were carried out at the strain ratio of 0.1. The cyclic deformation and the relationships between the strain amplitude, the stress amplitude, the Smith, Watson and Topper （SWT） parameter and fatigue life were studied and compared with those at the strain ratio of -I. Compared with other methods, Basquin formula and Solonberg formula provide reliable and appropriate ranges of S-N curve and fatigue limit at different strain ratios respectively. The SWT parameter can be used to predict the fatigue life at other strain ratios accurately.